Topsoil radiological characterisation of L-54M reactor surroundings preliminary to decommissioning operations. (January 2019) - Mossini, E.; Codispoti, L.; Giola, M.; Castelli, L.; Macerata, E.; Porta, A.; Campi, F.; Mariani, M.
Abstract: The radiological characterization of the topsoil of the L-54M reactor surroundings carried out in this work aims at obtaining the reference blank point for the forthcoming decommissioning operations and ascertain if unexpected radionuclide release occurred during the operational life of the plant. Standardised methods have been employed in order to collect representative samples and reliable results. Suitable sample pre-treatment procedures were applied. Gamma and beta spectrometric analyses were carried out to measure the activity concentrations of 60 Co 137 Cs, 152 Eu, 241 Am and 90 Sr. These have been considered as representative radionuclides that could have been originated from reactor operations and that could still be present at four decades post reactor shutdown. Highlights: Topsoil radiological survey before L-54M decommissioning operations. Sampling and sample treatments were with standardized methods. 60 Co, 90 Sr, 152 Eu and 241 Am below Minimum Detectable Activity concentrations. Activity concentration of 137 Cs is considerably below the EC RP 122 clearance level. No contamination was spread outside the L-54M reactor building.